STATUS OF MANGROVES IN SRI LANKA - K. M. B. C. Karunathilake (JOURNAL OF COASTAL DEVELOPMENT, 2003)
In Sri Lanka many estuaries and lagoons are fringed with vastly diverse mangrove forests. The total mangrove cover is very small as 0.1 to 0.2 percent of the total land area. The distribution of fauna and flora varies along with wet and dry zone in the country. Around 25 species of flora are exclusive to mangroves and more than 25 species can be identified as associated mangroves. Variety of invertebrates and vertebrates are conspicuous in the mangrove forests, but only a few species are confined to the ecosystem. Heavy utilization and reforestation for shrimp farms and building construction work severely affect on this ecosystem. When compare to decline rate of mangrove forests in Sri Lanka, current implemented conservation measures are inadequate.